PENGARUH KUALITAS JASA PENDIDIKAN TINGGI, MANAJEMEN KERELASIAN MAHASISWA TERHADAP CITRA UNIVERSITAS WIDYATAMA - Hasti Pramesti Kusnara (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The need for education in Indonesia is still very high. This is a large market share and an opportunity for formal education institutions. Global competition has also hit thr world of education. Every year, when the high school or vocational school graduates competing for selection instituttions, universities were competing promote themselves and attract potential student candidates. This thesis presents the results of survey of students at the Widyatama University Bandung. Data obtained by distributing questionnaires and as many as 235 students of all majors and the class of 2011 to 2015. The spread made online by sending a link online questionnaires has been designed in google docs. Structural Equation Modeling (SEM) was used to analyze and test the hypothesis of this study with the help of IBM SPSS application AMOS 20. The methods was used in this research is the methods of Maximum Likelihood Estimation (MLE). Results of this research may help to explain the effect of the quality of educational services and the management of the image of the university student kerelasian Widyatama which allows it to be used and developed in building the image og the university. The results showed that the model 1 and model 2 only there is influence the quality of education services to the image of the university, while students relationship management does not affect the image of the university. As for the 3 models found any influence of the quality of education and management services kerelasian students againts the university’s image. As the researchers suggest that as the dimensions of empathy and assurance because it is a very positive response classroom equipped with complete equipment and parking facilities are provided to note and expanded since contributed immensely in building the image of the university, while the students relationship management on the dimensions identify the students with a good database and provide convenience in obtaining information quickly through the acailability of the service enable this feature on the website.